Designing Healing Center for People with Mental Problems in Lembang, West Bandung Regency - Salafiyah, Jihan Salma; Damayanti, Setia (Journal of Aesthetics, Creativity and Art Management, 2024)
The 2018 Riskesdas results for provinces throughout Indonesia noted that the graph of mental disorders and depression in DKI Jakarta and West Java tends to increase from 2013 to 2018. The Least and Most Stressful Cities Index 2021 report also states that the city of Jakarta is a city with high levels of 9th highest stress in the world. The Healing Center for ODMK (Orang dengan Masalah Kejiawaan or People with Mental Problems) in Lembang, West Bandung Regency aims to provide a means of restoring health to the human mind. The authors used qualitative methods by collecting secondary and primary data through research journals, books/ebooks, and articles related to the research object. They also conducted a survey of the design location as analysis material. The results of the  analysis show that the basic recovery method that can be applied by many people is the Self Healing method so that in terms of building the appropriate theme is Healing Environment. The Healing Environment theme aims to create an environment that can heal. It is hoped that the Healing Center for the ODMK (People with Mental Problems) in Lembang, West Bandung Regency can be a solution for recovering a person's mental problems and providing sensitivity to mental health.